Question
upstudy study bank question image url

Solve the equation. Write your answers in exact, \[ 48 p^{3}+16 p^{2}-3 p-1=0 \] The solution set is \( \{\square\} \). \( \square, \ldots, \square \)

Ask by Fitzgerald Barker. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( p = -\frac{1}{3} \), \( p = -\frac{1}{4} \), and \( p = \frac{1}{4} \).

Solution

Solve the equation \( 48p^{3}+16p^{2}-3p-1=0 \). Solve the equation by following steps: - step0: Solve for \(p\): \(48p^{3}+16p^{2}-3p-1=0\) - step1: Factor the expression: \(\left(3p+1\right)\left(4p-1\right)\left(4p+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&3p+1=0\\&4p-1=0\\&4p+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&p=-\frac{1}{3}\\&p=\frac{1}{4}\\&p=-\frac{1}{4}\end{align}\) - step4: Rewrite: \(p_{1}=-\frac{1}{3},p_{2}=-\frac{1}{4},p_{3}=\frac{1}{4}\) The solution set for the equation \(48p^{3}+16p^{2}-3p-1=0\) is \(\left\{-\frac{1}{3}, -\frac{1}{4}, \frac{1}{4}\right\}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( 48 p^{3}+16 p^{2}-3 p-1=0 \), we can first look for rational roots using the Rational Root Theorem. After testing some values, we find that \( p = \frac{1}{4} \) is a root. We can then use synthetic division to divide the polynomial by \( p - \frac{1}{4} \). After performing the division, we are left with a quadratic equation: \[ 48 p^2 + 24 p + 4 = 0 \] We can simplify this by dividing every term by 4: \[ 12 p^2 + 6 p + 1 = 0 \] Next, we can apply the quadratic formula \( p = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): Here, \( a = 12 \), \( b = 6 \), and \( c = 1 \): \[ p = \frac{-6 \pm \sqrt{6^2 - 4(12)(1)}}{2(12)} \] \[ p = \frac{-6 \pm \sqrt{36 - 48}}{24} \] \[ p = \frac{-6 \pm \sqrt{-12}}{24} \] \[ p = \frac{-6 \pm 2i\sqrt{3}}{24} \] \[ p = \frac{-1 \pm \frac{i\sqrt{3}}{6}}{4} \] So the complete solution set is: \[ \left\{ \frac{1}{4}, \frac{-1}{4} + \frac{i\sqrt{3}}{12}, \frac{-1}{4} - \frac{i\sqrt{3}}{12} \right\} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy